Stabilizing controller design for uncertain nonlinear systems using fuzzy models - Teixeira, MCM; Zak, S. H. (Institute of Electrical and Electronics Engineers (IEEE), 1999)
A Lyapunov-based stabilizing control design method for uncertain nonlinear dynamical systems using fuzzy models is proposed. The controller is constructed using a design model of the dynamical process to be controlled. The design model is obtained from the truth model using a fuzzy modeling approach. The truth model represents a detailed description of the process dynamics. The truth model is used in a simulation experiment to evaluate the performance of the controller design. A method for generating local models that constitute the design model is proposed. Sufficient conditions for stability and stabilizability of fuzzy models using fuzzy state-feedback controllers are given. The results obtained are illustrated with a numerical example involving a four-dimensional nonlinear model of a stick balancer.
Keywords: fuzzy modeling; Lyapunov's method; stability; uncertain systems